Method for producing active material

By mixing an alkali metal compound with an electrode mixture and heating it in a high oxygen partial pressure atmosphere, the method addresses the crystal structure deterioration issue, resulting in high-capacity active materials.

JP7605932B2Active Publication Date: 2024-12-24SUMITOMO CHEM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023175936
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2024-12-24
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

The deterioration of the crystal structure of active materials during the reproduction process leads to a decrease in charge and discharge capacity, necessitating a method to suppress this deterioration.

Method used

A method involving mixing an activation treatment agent containing one or more alkali metal compounds with an electrode mixture, heating the mixture to a temperature higher than the melting start temperature of the activation treatment agent in an atmosphere with an oxygen partial pressure of 0.3 atm or higher, and recovering the active material.

Benefits of technology

The method effectively suppresses the deterioration of the crystal structure, enabling the production of active materials with a discharge capacity of 150 mAh/g or more.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605932000001
    Figure 0007605932000001
  • Figure 0007605932000002
    Figure 0007605932000002
Patent Text Reader

Abstract

To provide a method of manufacturing an active material capable of suppressing deterioration of a crystal structure.SOLUTION: Provided is a method of manufacturing an active material, the method including the following steps of: (1) mixing an activation treatment agent containing an alkali metal compound to an electrode mixture containing the active material and a binding material; (2) heating the mixture to a temperature equal to or higher than a melting start temperature of the activation treatment agent under an oxygen partial pressure equal to or higher than 0.7 atm; and (3) collecting the active material. The active material is a composite oxide represented by Li1+aM2bM1MTcO2+dXe. Here, M2 represents one or more elements selected from Na, K, Ca, Sr, Ba, and Mg; and M1 represents one kind of element selected from Ni, Co, Mn, Fe, Al, and P; and MT represents one element selected from transition metal elements other than Ni, Co, Mn, and Fe; and X represents one or more elements selected from non-metal elements except oxygen O and P, and relations of -0.4<a<1.5, 0≤b<0.5, 0≤c<0.5, -0.5<d<1.5, and 0≤e<0.5 are satisfied.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an active material. [Background technology]

[0002] The active material of a battery contains rare metal components such as cobalt, nickel, manganese, and lithium, and in particular, the positive electrode active material of a non-aqueous electrolyte secondary battery uses a compound mainly composed of the above rare metal components. In order to conserve the resources of rare metal components, a method for reproducing the rare metal components from waste battery materials of secondary batteries is required.

[0003] For example, Patent Document 1 discloses a method of recovering active material by mixing an electrode mixture with an activation treatment agent containing an alkali metal compound, heating the mixture to decompose the binder, and removing the decomposition product and the activation treatment agent with water or the like. This method is cost-effective in that it does not use organic solvents and directly recovers active material from battery waste. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-186150 A Summary of the Invention [Problem to be solved by the invention]

[0005] In order to effectively reuse the recycled active material, it is necessary to suppress the deterioration of the crystal structure of the active material before and after the recycling process. If the crystal structure of the active material deteriorates, it leads to a decrease in the charge / discharge capacity, which is undesirable.

[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a method for producing an active material that is capable of suppressing deterioration of the crystal structure. [Means for solving the problem]

[0007] The method for producing an active material according to the present invention includes the following steps. (1) A step of mixing an activation treatment agent containing one or more alkali metal compounds with an electrode mixture containing an active material and a binder. (2) heating the mixture obtained in an atmosphere having an oxygen partial pressure of 0.3 atm or more to a temperature equal to or higher than the melting temperature of the activation treatment agent; (3) recovering the active material from the heated mixture.

[0008] Here, the active material may be a positive electrode active material, and may also be a positive electrode active material for a non-aqueous secondary battery.

[0009] The active material may be a composite oxide containing one or more elements selected from the following element group 1 and one or more elements selected from element group 2. Element group 1: Ni, Co, Mn, Fe, Al, P Element group 2: Li, Na, K, Ca, Sr, Ba, Mg

[0010] The active material is Li 1+a M 2 b M 1 M T c O 2+d X e The compound oxide may be represented by the formula: However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg; M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P; M T represents at least one element selected from the group consisting of transition metal elements other than Ni, Co, Mn, and Fe; X represents at least one element selected from the group consisting of nonmetallic elements excluding oxygen (O) and P; -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, 0 ≤ e < 0.5 are satisfied.

[0011] Also, M in the composite oxide 1 The molar fraction of Ni contained in it can be 0.5 or more.

[0012] Also, the composite oxide can have a hexagonal crystal structure.

[0013] Also, the discharge capacity of the recovered active material can be 150 mAh / g or more.

[0014] Also, at least one alkali metal compound contained in the activation treatment agent can contain the same alkali metal element as the alkali metal element contained in the active material.

[0015] Also, at least one of the alkali metal compounds contained in the activation treatment agent can be an alkali metal compound that shows alkalinity when dissolved in water.

[0016] Also, the alkali metal compound that shows alkalinity when dissolved in water can be one or more selected from the group consisting of alkali metal hydroxides, carbonates, bicarbonates, oxides, peroxides, and superoxides.

[0017] Also, the melting start temperature of the activation treatment agent can be 700°C or lower.

Advantages of the Invention

[0018] According to the present invention, the active material can be produced from the electrode binder while suppressing the deterioration of the crystal structure.

Embodiments for Carrying Out the Invention

[0019] Hereinafter, embodiments of the present invention will be described.

[0020] The method for producing an active material according to an embodiment of the present invention includes the following steps. (1) A step of mixing an activation treatment agent containing one or more alkali metal compounds with an electrode mixture containing an active material and a binder. (2) heating the mixture obtained in an atmosphere having an oxygen partial pressure of 0.3 atm or more to a temperature equal to or higher than the melting temperature of the activation treatment agent; (3) recovering the active material from the heated mixture. Hereinafter, each step in the method for recovering active material from waste battery materials according to the present invention will be described in detail.

[0021] Step (1): A step of mixing an activation treatment agent with an electrode mixture. First, an electrode mixture is prepared.

[0022] <Electrode composite material> The electrode mixture is a material containing an active material and a binder, and the active materials are bound to each other by the binder. The electrode mixture may further contain a conductive material, and in that case, the active material and the conductive material are bound to each other by the binder.

[0023] <Active material> The active material may be a positive electrode active material or a negative electrode active material.

[0024] Examples of the positive electrode active material are composite compounds containing lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, tungsten, or the like as constituent elements.

[0025] Examples of the negative electrode active material are composite compounds containing lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, tungsten, or the like as constituent elements.

[0026] The active material may be composed of only a single compound, or may be composed of a plurality of compounds.

[0027] Examples of suitable positive electrode active materials are composite compounds containing lithium, oxygen, sodium, potassium, calcium, magnesium, aluminum, phosphorus, sulfur, vanadium, manganese, iron, nickel, copper, cobalt, gallium, molybdenum, indium, tungsten, or the like as constituent elements.

[0028] The active material in the present invention is preferably a positive electrode active material for a non-aqueous secondary battery. An example of the positive electrode active material for a non-aqueous secondary battery is a composite oxide containing one or more elements selected from the following element group 1 and one or more metals selected from element group 2. Element group 1: Ni, Co, Mn, Fe, Al, P Element group 2: Li, Na, K, Ca, Sr, Ba, Mg

[0029] Among these, preferred are lithium transition metal composite oxides in which element group 1 is one or more selected from Ni, Co, Mn, Fe, and P, and element group 2 is Li, or sodium transition metal composite oxides in which element group 2 is Na, and particularly preferred are lithium transition metal composite oxides.

[0030] Specifically, examples of lithium transition metal composite oxides include LiCoO2, LiNiO2, Li(Ni,Co)O2, Li(Ni,Co,Al)O2, Li(Ni,Mn)O2, Li(Ni,Mn,Co)O2, LiMn2O4, Li(Mn,Fe)2O4, Li2MnO3, Li2NiO3, Li2(Ni,Mn)O3, LiFePO4, LiMnPO4, etc., and these can be used alone or in combination of two or more.

[0031] Examples of the sodium transition metal composite oxides include, specifically, NaCoO2, NaNiO2, Na(Ni,Co)O2, Na(Ni,Mn)O2, Na(Ni,Mn,Co)O2, Na(Fe,Ni,Mn)O2, NaMn2O4, Na(Mn,Fe)2O4, NaFePO4, NaMnPO4, etc., and these can be used alone or in combination of two or more kinds.

[0032] In particular, it is preferable that the composite oxide is represented by Li 1+a M 2 b M 1 M T c O 2+d X e (Formula A). However, M 2 represents at least one element selected from the group consisting of Na, Ca, Sr, Ba, and Mg, M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P, M T represents at least one element selected from the group consisting of transition metal elements other than Ni, Co, Mn, and Fe, X represents at least one element selected from the group consisting of non-metal elements excluding oxygen O and P, and -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, 0 ≤ e < 0.5 are satisfied. Examples of X are F, Cl, Br, I, S, Se, Te, and N.

[0033] The molar fraction of Ni contained in M 1 in the composite oxide can be 0.5 or more, and may be 0.6 or more, 0.7 or more, or 0.8 or more.

[0034] The crystal structure of the above composite oxide as the active material is not particularly limited, but a preferable crystal structure is a layered structure. More preferably, a hexagonal or monoclinic crystal structure is preferable.

[0035] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P6 3, it belongs to any one space group selected from the group consisting of P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm and P63 / mmc.

[0036] The monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c and C2 / c.

[0037] Furthermore, it preferably belongs to the space group R-3m contained in a hexagonal crystal structure or the space group C2 / m contained in a monoclinic crystal structure.

[0038] The crystal structure of the active material is identified from a powder X-ray diffraction pattern obtained by powder X-ray diffraction measurement using CuKα radiation as a radiation source.

[0039] There is no particular limit to the particle diameter of the active material in the electrode mixture. It is usually about 0.001 to 100 μm. The particle size distribution of the active material can be measured using a laser diffraction scattering particle size distribution measuring device (for example, Malvern Mastersizer 2000). From the obtained particle size distribution, a volume-based cumulative particle size distribution curve can be created, and the particle diameter (D50) value at 50% accumulation from the fine particle side can be taken as the average particle diameter of the powder. The particle diameter of the primary particles of the active material can be measured as the arithmetic mean of the circle-equivalent diameter in an electron microscope photograph.

[0040] <Conductive material> Examples of the conductive material include metal-based conductive materials such as metal particles, and carbon-based conductive materials made of carbon materials.

[0041] Examples of carbon-based conductive materials are specifically graphite powder, carbon black (eg, acetylene black), and fibrous carbon materials (eg, graphitized carbon fibers, carbon nanotubes).

[0042] The carbon-based conductive material may be a single carbon material, or may be composed of a plurality of carbon materials.

[0043] The specific surface area of ​​the carbon material used as the carbon-based conductive material is usually 0.1 to 500 m 2 / g.

[0044] In this case, the conductive material is 30m 2 / g or more, it can be made of only carbon-based conductive materials 2 / g or more of carbon black, 2 / g or more.

[0045] When an activation treatment agent containing an alkali metal compound having an oxidizing power, which will be described later, is used, the speed of the oxidation treatment of the carbon-based conductive material can be increased, and even carbon materials having a small specific surface area can sometimes be oxidized.

[0046] <Binding material> Examples of the binder (pre-activation treatment binder) contained in the electrode mixture are thermoplastic resins, and specific examples thereof include fluororesins such as polyvinylidene fluoride (hereinafter sometimes referred to as PVdF), polytetrafluoroethylene (hereinafter sometimes referred to as PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (hereinafter sometimes referred to as SBR); and mixtures of two or more of these may be used.

[0047] There is no particular limitation on the amounts of active material, conductive material, and binder in the electrode mixture. The amount of binder can be 0.5 to 30 parts by weight, or may be 1 to 5 parts by weight, relative to 100 parts by weight of the positive electrode active material. The amount of conductive agent can be 0, or may be 0 to 50 parts by weight, or may be 1 to 10 parts by weight, relative to 100 parts by weight of the positive electrode active material.

[0048] Such an electrode mixture can be obtained by separating and recovering the electrode mixture from a waste electrode having a current collector and an electrode mixture layer.

[0049] The term "waste electrodes" refers to electrodes recovered from discarded batteries and electrode waste generated during the manufacturing process of electrodes and batteries. The discarded batteries may be used batteries or unused but non-standard batteries. The electrode waste may be the ends of electrodes generated during the battery manufacturing process and non-standard electrodes. In addition, waste electrode composites that are not attached to current collectors and are generated during the electrode composite manufacturing process may also be used.

[0050] The electrode has a current collector which is a metal foil such as an aluminum foil or a copper foil, and an electrode mixture layer provided on the current collector. The electrode mixture layer may be provided on one side or both sides of the current collector.

[0051] Methods for separating the electrode mixture from an electrode having an electrode mixture layer and a current collector include a method of mechanically peeling the electrode mixture layer from the current collector (for example, a method of scraping the electrode mixture from the current collector), a method of penetrating a solvent into the interface between the electrode mixture layer and the current collector to peel the electrode mixture layer from the current collector, a method of dissolving the current collector using an alkaline or acidic aqueous solution to separate the electrode mixture layer, etc. The method of mechanically peeling the electrode mixture layer from the current collector is preferred.

[0052] The electrode may be either a positive electrode or a negative electrode. A positive electrode mixture can be recovered from the positive electrode, and a negative electrode mixture can be recovered from the negative electrode. A positive electrode active material can be recovered by using a positive electrode mixture, and a negative electrode active material can be recovered by using a negative electrode mixture. The method for producing an active material of the present invention is suitably applied to the recovery of a positive electrode active material from a positive electrode mixture, and is suitably applied to the positive electrode active material of a non-aqueous secondary battery, among other positive electrode active materials.

[0053] Next, an activation treatment agent containing one or more alkali metal compounds is mixed with the prepared electrode mixture.

[0054] The electrode mixture and the activation treatment agent may be mixed by either dry mixing or wet mixing, or by a combination of these mixing methods, and the mixing order is not particularly limited.

[0055] During mixing, it is preferable to use a mixer equipped with mixing media such as balls and to carry out a pulverizing and mixing step, which can improve the mixing efficiency.

[0056] Dry mixing is preferred because mixing can be performed more easily. For dry mixing, a V-type mixer, W-type mixer, ribbon mixer, drum mixer, powder mixer equipped with stirring blades inside, ball mill, vibration mill, or a combination of these devices can be used.

[0057] A specific example of a suitable powder mixer having an internal stirring blade is the Loedige Mixer (manufactured by Matsubo Corporation).

[0058] The activation treatment agent used in this step will be described in detail below.

[0059] <Activation treatment agent> The activation treatment agent contains one or more alkali metal compounds. When the alkali metal compound comes into contact with the active material, the active material can be activated. When the alkali metal compound in the activation treatment agent contains a molten portion, the contact between the molten portion and the active material is improved, and the activation of the active material is further promoted.

[0060] In addition, the electrode mixture may contain a compound containing fluorine derived from the binder and / or the electrolyte, but by contacting the compound containing fluorine with the activation treatment agent, the fluorine component is stabilized as an alkali metal fluoride, so that the generation of corrosive gases such as hydrogen fluoride can be suppressed. Note that it is desirable to prevent the generation of hydrogen fluoride, since it reduces the activity of the active material.

[0061] The proportion of the alkali metal compound in the activation treatment agent is appropriately set taking into consideration the type of alkali metal compound and the type of target active material, etc., but is usually 50% by weight or more, preferably 70% by weight or more (including 100% by weight) of the total weight of the activation treatment agent.

[0062] Examples of alkali metal compounds that are components of the activation treatment agent include hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, and tungstates of alkali metals. These can be used alone or in combination as components of the activation treatment agent.

[0063] The alkali metal element constituting the alkali metal compound may be any alkali metal element, and is preferably at least one selected from the group consisting of lithium, sodium, and potassium. When two or more types of alkali metal compounds are contained as components of the activation treatment agent, they may be alkali metal compounds containing different alkali metal elements.

[0064] Specific examples of suitable alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, CsOH, etc.; Borates such as LiBO2, NaBO2, KBO2, RbBO2, CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; Oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4; Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.

[0065] Here, in order to further enhance the activation effect of the active material, at least one type of alkali metal compound contained in the activation treatment agent may contain the same alkali metal element as the alkali metal element contained in the active material in the electrode mixture.

[0066] That is, when the active material in the electrode mixture is a lithium composite oxide, the alkali metal compound in the activation treatment agent (at least one of the alkali metal compounds when two or more types are used) can be a lithium compound. Suitable lithium compounds include LiOH, LiBO2, Li2CO3, Li2O, Li2O2, LiO2, LiNO3, Li3PO4, Li2SO4, LiCl, LiVO3, LiBr, Li2MoO4, and Li2WO4.

[0067] In addition, when the active material in the electrode mixture is a sodium composite oxide, the alkali metal compound in the activation treatment agent (at least one of the compounds when two or more compounds are used) may be a sodium compound. Suitable sodium compounds include NaOH, NaBO2, Na2CO3, Na2O, Na2O2, NaO2, NaNO3, Na3PO4, Na2SO4, NaCl, NaVO3, NaBr, Na2MoO4, and Na2WO4.

[0068] The activation treatment agent may contain a compound other than an alkali metal compound as necessary. Examples of the compound other than an alkali metal compound include alkaline earth metal compounds containing alkaline earth metal elements such as magnesium, calcium, barium, etc. The alkaline earth metal compound is contained in the activation treatment agent together with the alkali metal compound for the purpose of controlling the melting start temperature of the activation treatment agent.

[0069] In addition, the content of compounds other than the alkali metal compound in the activation treatment agent is selected within a range that does not significantly suppress the effects derived from the above-mentioned molten alkali metal compound, and is less than 50% by weight of the total weight of the activation treatment agent.

[0070] The amount of the activation treatment agent added in the mixture of the electrode mixture and the activation treatment agent is preferably 0.001 to 100 times, and more preferably 0.05 to 1 time, the weight of the active material contained in the electrode mixture.

[0071] The number of moles of the alkali compound in the activation treatment agent in the mixture of the electrode mixture and the activation treatment agent can be such that the number of moles of alkali atoms is 0.001 to 200 times the number of moles of the active material (e.g., Formula A) contained in the electrode mixture, which is taken as 1.

[0072] By appropriately controlling the ratio of the activation treatment agent in the mixture, it is possible to reduce the cost of recovering the active material from the electrode mixture, increase the oxidative decomposition rate of the carbon-based conductive material and the binder, improve the effect of preventing the generation of corrosive gas in the activation treatment step, and further increase the discharge capacity of the battery produced using the obtained active material.

[0073] In addition, it is preferable that at least one of the alkali metal compounds contained in the activation treatment agent is an alkali metal compound that exhibits alkalinity when dissolved in water. When an activation treatment agent containing such an alkali metal compound is dissolved in pure water, the pH of the solution becomes greater than 7. Hereinafter, such an activation treatment agent may be referred to as an "alkaline activation treatment agent."

[0074] In the present invention, the use of an alkaline activation treatment agent can further suppress the generation of corrosive gases during the heating process, thereby further increasing the discharge capacity of a battery produced using the recovered active material. In addition, the use of an alkaline activation treatment agent can also increase the treatment speed of the carbon-based conductive material and the binder.

[0075] Examples of alkali metal compounds that exhibit alkalinity when dissolved in water and are contained in an alkaline activation treatment agent include hydroxides, carbonates, hydrogen carbonates, oxides, peroxides, and superoxides of alkali metals.Specific examples include LiOH, NaOH, KOH, RbOH, and CsOH; Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; LiHCO3, NaHCO3, KHCO3, RbHCO3, CsHCO3; Li2O, Na2O, K2O, Rb2O, and Cs2O; Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; LiO2, NaO2, KO2, RbO2, and CsO2; and these may be contained in the activation treatment agent alone or in combination.

[0076] In addition, when the conductive material contained in the electrode mixture is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activation treatment agent may be an alkali metal compound having an oxidizing power that oxidizes and decomposes the carbon-based conductive material at the temperature of the activation treatment step. Hereinafter, an activation treatment agent containing such an alkali metal compound may be referred to as an "activation treatment agent having an oxidizing power."

[0077] The use of an activation treatment agent having such an oxidizing power is particularly effective in promoting the oxidation of the conductive material, which is a carbon material, to carbon dioxide, and promoting the oxidation of the binder, which is a hydrocarbon material, to carbon dioxide and water vapor, and can further increase the discharge capacity of a battery produced using the obtained active material, and can also improve the effect of preventing the generation of corrosive gases in the activation treatment process.

[0078] Alkali metal compounds having the oxidizing power necessary to oxidize the carbonaceous conductive material and the hydrocarbons to carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates, which may be used alone or in combination of two or more.

[0079] Specifically, these include Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; LiO2, NaO2, KO2, RbO2, CsO2; LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4;

[0080] Details of the oxidizing power of these alkali metal compounds are described in JP 2012-186150 A.

[0081] Step (2): <Step of heating the mixture> The heating step is a step of heating the mixture obtained in step (1) (hereinafter sometimes referred to as the "pre-heated mixture") to a temperature equal to or higher than the melting initiation temperature of the activation treatment agent in an atmosphere having an oxygen partial pressure of 0.3 atm or higher.

[0082] The "melting start temperature (Tmp) of the activation treatment agent" means the lowest temperature at which a part of the activation treatment agent exhibits a liquid phase.

[0083] In the present invention, the melting start temperature (Tmp) of the activation treatment agent is a value determined by differential thermal analysis (DTA). That is, 5 mg of the above mixture is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting start temperature (Tmp). The melting start temperature (Tmp) of the activation treatment agent is preferably 700° C. or lower, and may be 600° C. or lower. There is no lower limit to the melting start temperature (Tmp) of the activation treatment agent, but it may be, for example, 150° C.

[0084] The melting point of the activation treatment agent means the lowest temperature at which a part of the activation treatment agent becomes liquid when the activation treatment agent alone is heated. By mixing the electrode mixture and the activation treatment agent, the melting start temperature of the activation treatment agent becomes lower than the melting point of the activation treatment agent.

[0085] In the present invention, the melting point of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, 5 mg of the activation treatment agent is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10° C. / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting point of the activation treatment agent.

[0086] The atmosphere in the heating may have an oxygen partial pressure of 0.3 atm or more, and may be 0.4 atm or more, 0.5 atm or more, 0.6 atm or more, 0.7 atm or more, 0.8 atm or more, 0.9 atm or more, or 1.0 atm or more. Note that 1 atm is 101325 Pa. There is no particular limitation on the total pressure of the atmosphere, and it may be atmospheric pressure, a reduced pressure atmosphere, or a pressurized atmosphere.

[0087] Examples of gases other than oxygen in the atmosphere are nitrogen, argon, and carbon dioxide.

[0088] In step (2), the mixture is heated to a temperature equal to or higher than the melting temperature of the activation treatment agent in an atmosphere having an oxygen partial pressure of 0.3 atm or higher, as described above, whereby the following effects occur.

[0089] In an atmosphere with a high oxygen partial pressure, the activating agent in a molten state comes into contact with the active material, thereby suppressing deterioration of the crystal structure of the active material and, in some cases, even achieving a repair effect on the crystal structure.

[0090] In addition, when the molten activation treatment agent comes into contact with the carbon-based conductive material and binder, the rate of oxidative decomposition of the conductive material and binder is increased, and further, when the molten activation treatment agent comes into contact with the binder and a fluorine compound derived from the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the active material.

[0091] Furthermore, when the activation treatment agent contains the same alkali metal as the active material, it is possible to supply the active material with the alkali metal that is insufficient.

[0092] The temperature of the heating step and the holding time at that temperature can be appropriately adjusted depending on the types and combinations of the active material, conductive material, and binder constituting the electrode mixture, and the alkali metal compound and other compounds contained in the activation treatment agent. Usually, the temperature is in the range of 100 to 1500°C, and the holding time is about 10 minutes to 24 hours.

[0093] The temperature is preferably higher than the melting point of the alkali metal compound contained in the activation treatment agent. The melting point of the alkali metal compound may be lower than the melting point of each compound alone by mixing multiple types of compounds. When the activation treatment agent contains two or more types of alkali metal compounds, the eutectic point is the melting point of the alkali metal compound.

[0094] After the heating step, the mixture can be cooled to any temperature, such as, for example, about room temperature, if desired.

[0095] Step (3): <Step of recovering active material> Step (3): A step of recovering the active material is a step of recovering the active material from the mixture after the heating step of step (2).

[0096] The mixture that has undergone the heating process contains, in addition to the active material, components derived from the activation treatment agent (such as alkali metal compounds), undecomposed conductive materials and binders, and other undecomposed materials of the electrode mixture. In addition, if the electrode mixture contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte.

[0097] Examples of methods for separating and recovering the active material from the mixture that has been subjected to the heating step include a slurry solid-liquid separation method in which a solvent such as water is added to the mixture to form a slurry, followed by solid-liquid separation, and a vaporization separation method in which the mixture is heated to vaporize and separate components other than the active material.

[0098] The slurry solid-liquid separation method, which is a preferred method for the active material recovery step, will be described in detail below.

[0099] <Slurry solid-liquid separation method> The active material recovery process using the slurry solid-liquid separation method includes a slurrying step of adding a solvent to the mixture obtained after the activation treatment step to form a slurry, a solid-liquid separation step of separating the slurry into a solid phase and a liquid phase, and a drying step of drying the solid phase after solid-liquid separation.

[0100] This method is particularly suitable for recovering water-insoluble active materials.

[0101] The slurrying step is a step of adding a solvent to the mixture after the activation treatment to prepare a slurry.

[0102] There are no limitations on the solvent used in the slurrying process, so long as it can dissolve the components other than the active material contained in the mixture. Water is preferable as the solvent, as it is inexpensive and easy to use industrially. In order to increase the solubility of the water-soluble components or to increase the processing speed, components other than water may be added to adjust the pH.

[0103] In the slurrying process, a slurry is produced that contains a solid phase mainly containing the active material and a liquid phase containing water-soluble components other than the active material. The liquid phase contains an alkali metal component derived from the activation treatment agent and / or a fluorine component derived from the binder and the electrolyte.

[0104] The amount of the solvent to be added to the mixture is appropriately determined taking into consideration the amounts of the active material and water-soluble components other than the active material contained in the mixture.

[0105] The slurry formed in the slurrying step is then subjected to a solid-liquid separation step. The solid-liquid separation step is a step in which the slurry is separated into a liquid phase and a solid phase. The method for solid-liquid separation may be a conventionally known method, for example, filtration or centrifugation.

[0106] The drying step is a step in which the active material obtained after the solid-liquid separation step is dried to remove the solvent (water).

[0107] The drying temperature is preferably 100°C or higher to remove the solvent (moisture). It is more preferably 150°C or higher to thoroughly remove moisture. A temperature of 250°C or higher is particularly preferred because it further increases the discharge capacity of a battery produced using the resulting active material. The temperature in the drying step may be constant or may be changed stepwise or continuously.

[0108] After drying, the active material may be re-fired in an oxygen-containing atmosphere, such as an air atmosphere, or in an atmosphere with an oxygen partial pressure of 0.3 atm or more, similar to the heating step.

[0109] The re-firing temperature can be 100 to 1500°C.

[0110] The holding time for re-firing can be from 1 minute to 24 hours.

[0111] The active material obtained from the battery mix by using the method for producing the active material of the present invention can be reused in the same way as unused active material. Methods for producing electrodes and batteries using the active material are well known.

[0112] The discharge capacity of the recovered active material can be 150 mAh / g or more.

[0113] The molar ratio of alkali metal to transition metal in the produced active material is preferably equal to or greater than that in the active material in the electrode mixture. By increasing the alkali metal ratio, the discharge capacity of a battery produced using the resulting active material can be increased. EXAMPLES

[0114] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.

[0115] Measurement of the physical properties of the active material (before the production of an electrode mixture) and a charge / discharge test using a battery using the active material as a positive electrode active material were carried out as follows.

[0116] (1) Composition analysis The sample was dissolved in hydrochloric acid, and then the composition was analyzed using inductively coupled plasma atomic emission spectrometry (hereinafter sometimes referred to as ICP-AES) (using SPS3000 manufactured by SII NanoTechnology Inc.).

[0117] (2) Powder X-ray diffraction measurement Powder X-ray diffraction measurement of the samples was performed using a powder X-ray diffraction measuring device X'Pert PRO manufactured by Spectris Corporation. A CuKα source was used as the X-ray source. The active material was filled into a dedicated holder, and measurements were performed at a diffraction angle 2θ of 10 to 90° to obtain a powder X-ray diffraction pattern. Based on the obtained powder X-ray diffraction pattern, the lattice constants were refined by the least squares method using PDXL2 software manufactured by Rigaku Corporation, and the interplanar spacing of the (110) plane was obtained. Measurement equipment: Powder X-ray diffraction measurement equipment X'Pert PRO manufactured by Spectris Corporation X-ray generator: CuKα source, voltage 45kV, current 40mA Slit: 1° Scan step: 0.02deg Scan range: 10-90deg Scan speed: 4deg / min X-ray detector: One-dimensional semiconductor detector Measurement atmosphere: Air Sample stage: Dedicated glass sample plate

[0118] (3) Measurement of pH of activation treatment agent 3.5 g of the activating treatment agent was added to 70 g of pure water and thoroughly stirred with a stirrer, and the pH was measured using a pH meter with a glass electrode.

[0119] (4) Measurement of the melting temperature of the activation treatment agent by differential thermal analysis (DTA) 5 mg of the mixture of the electrode mixture and the activation treatment agent was subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10° C. / min), and the temperature at which the DTA signal showed an endothermic peak was determined as the melting initiation temperature (Tmp). Differential thermal analysis (DTA) measurement conditions Equipment: Differential thermal and thermogravimetric simultaneous measurement equipment (TG / DTA6200) manufactured by Seiko Instruments Inc. Bread: Platinum Initial sample amount: 5mg Atmosphere: Air Heating rate: 10℃ / min

[0120] (5) Charge / discharge test 1. Preparation of the electrode (positive electrode) In order to measure the discharge capacity of the active material, an electrode (positive electrode) was prepared according to the following procedure.

[0121] Each active material, a binder (PVdF#1100 (manufactured by Kureha Corporation)), and a conductive material (acetylene black (manufactured by Denki Kagaku Kogyo Kabushiki Kaisha, product number: Denka Black HS100) were mixed so that the weight ratio of active material: binder: conductive material was 92:3:5, respectively, and the mixture was kneaded in an agate mortar to prepare a positive electrode composite paste.

[0122] As the binder solution, an NMP solution in which PVdF, a binder, was dissolved was used, and NMP was added to adjust the total weight of the active material, conductive material, and binder in the positive electrode mixture paste to 50% by weight.

[0123] The positive electrode mixture paste was applied to an Al foil current collector (3 × 5 cm), and the amount of electrode mixture was 3 mg / cm. 2 After coating so as to obtain a positive electrode, the mixture was dried in vacuum at 150° C. for 8 hours.

[0124] 2. Battery Construction The above-mentioned positive electrode, the electrolyte, the separator, and the negative electrode were combined to prepare a non-aqueous electrolyte secondary battery (coin-type battery R2032). The battery was assembled in a glove box in an argon atmosphere.

[0125] The electrolyte used was a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 30:70, in which LiPF6 was dissolved as an electrolyte at 1 mol / L.

[0126] The separator used was a laminated film separator in which a heat-resistant porous layer was laminated on a polyethylene porous film, and metallic lithium was used as the negative electrode.

[0127] 3.Charge / discharge test Using the produced coin-type battery, a charge-discharge test was carried out under the following conditions at 25° C. In the charge-discharge test, the discharge capacity was measured by changing the discharge current during discharge.

[0128] Maximum charging voltage: 4.3V Charging time: 8 hours Charging current: 40mA / g-active material (charging current is 40mA per 1g of active material) During discharge, the minimum discharge voltage was kept constant at 2.5 V, and the discharge current in each cycle was changed as follows.

[0129] Discharge cycle 1 (0.2C): Discharge current 40mA / g-active material Discharge cycle 2 (0.2C): Discharge current 40mA / g-active material 3rd cycle discharge (1C): Discharge current 200mA / g-active material 4th cycle discharge (2C): Discharge current 400mA / g-active material 5th cycle discharge (5C): Discharge current 1000mA / g-active material 6th cycle discharge (10C): Discharge current 2000mA / g-active material It is shown that the larger the 0.2C discharge capacity, the higher the rated capacity that can be obtained, and the larger the 5C discharge capacity, the higher the output characteristics that can be obtained.

[0130] Examples and Comparative Examples A. Preparation of positive electrode A

[0131] The active material is Li 1.06Ni 0.80 Co 0.11 Mn 0.09 The positive electrode active material used was O2 and had a crystal structure of R-3m. The 0.2C discharge capacity measured in a charge-discharge test using a coin-type battery that used this active material (unused active material) as the positive electrode active material was 184mAh / g. Another active material is Li 1.04 Ni 0.34 Co 0.33 Mn 0.33 The positive electrode active material used was O2 and had a crystal structure of R-3m. The discharge capacity at 0.2C measured in a charge-discharge test using a coin-type battery that used this active material (unused active material) as the positive electrode active material was 150mAh / g.

[0132] Acetylene Black HS100 (manufactured by Denki Kagaku Kogyo Co., Ltd.) was used as the conductive material.

[0133] The binder and solvent were prepared by adding NMP solvent to an NMP solution (manufactured by Kureha Corporation) containing 12% by weight of PVdF#1100 as the binder to obtain a predetermined ratio.

[0134] The mass ratio of the active material, binder, and conductive material in the positive electrode mixture was 92: 3: 5. The blending amount of the solvent was 50 mass % with respect to the entire positive electrode mixture paste.

[0135] The positive electrode mixture paste was applied onto a 20 μm-thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector in lithium-ion secondary batteries using a doctor blade coater, and then dried to obtain a positive electrode A. The amount of the electrode mixture on the aluminum foil was 20 mg / cm. 2 It was.

[0136] B. Recovery of electrode mixture from positive electrode A The electrode mixture was mechanically scraped off from the positive electrode A, and the electrode mixture was peeled off from the current collector.

[0137] C. Activation treatment agent mixing process A predetermined amount of activation agent (one or more alkali metal compounds) was added to the peeled electrode mixture and mixed in a mortar to obtain a mixture. The composition of the activation agent, the number of moles of each alkali metal compound per mole of the active material in the electrode mixture, the pH of the activation agent, and the melting start temperature of the activation agent measured separately for the mixture are shown in Table 1.

[0138] D. Heating process The obtained mixture (mixture before activation treatment) was placed in an alumina firing container and placed in an electric furnace. It was heated to a predetermined temperature under atmospheric pressure and in an atmosphere containing a predetermined oxygen concentration. The temperature was held for 4 hours, the heating rate to the temperature was 250°C / hour, and cooling to room temperature was performed by natural cooling. The oxygen concentration in the atmosphere was adjusted by adding additional oxygen to the air. The heating temperature, total pressure, oxygen concentration, and oxygen partial pressure are shown in Table 1.

[0139] E. Active material recovery process After the activation treatment, the mixture was pulverized, water was added to form a slurry, and the slurry was stirred and then decanted. The slurry was then filtered to separate the solid phase. The solid phase was then dried in vacuum at 100°C.

[0140] For the recovered active material (treated active material) and the active material before the production of positive electrode A (pre-treated active material), the (110) interplanar spacing was measured by powder X-ray diffraction measurement, and the discharge capacity was measured in a charge-discharge test.

[0141] Table 1 shows the conditions, and Table 2 shows the (110) interplanar spacing and the discharge capacity at 0.2 C of the active materials before and after the treatment in each of the examples and comparative examples.

[0142] [Table 1]

[0143] [Table 2] In the examples, it was confirmed that the change in the (110) interplanar spacing was small, and the deterioration of the crystal structure was small. On the other hand, in the comparative examples, it was confirmed that the change in the (110) interplanar spacing was large, and the deterioration of the crystal structure was large. The discharge capacity also showed a similar tendency.

Claims

1. A method for producing an active material comprising the steps of: The active material is Li 1+a M 2 b M 1 M T c O 2+d X e The present invention relates to a method for producing an active material, which is a composite oxide represented by the following formula: (1) A step of mixing an activation treatment agent containing one or more alkali metal compounds with an electrode mixture containing an active material and a binder. (2) Heating the mixture to a temperature equal to or higher than the melting temperature of the activation treatment agent in an atmosphere having an oxygen partial pressure of 0.7 atm or more. (3) A step of recovering the active material from the mixture after the heating. However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg; M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P; M T represents at least one element selected from the group consisting of transition metal elements other than Ni, Co, Mn, and Fe; X represents at least one element selected from the group consisting of nonmetallic elements excluding oxygen (O) and P; The following conditions are satisfied: −0.4<a<1.5, 0≦b<0.5, 0≦c<0.5, −0.5<d<1.5, 0≦e<0.

5.

2. The method for producing an active material according to claim 1 , wherein the active material is a positive electrode active material.

3. The method for producing an active material according to claim 2 , wherein the positive electrode active material is a positive electrode active material for a non-aqueous secondary battery.

4. M in the composite oxide 1 The method for producing an active material according to any one of claims 1 to 3, wherein a molar fraction of Ni contained in

5. The method for producing an active material according to any one of claims 1 to 4, wherein the composite oxide has a hexagonal crystal structure.

6. The method for producing an active material according to any one of claims 1 to 5, wherein the discharge capacity of the recovered active material is 150 mAh / g or more.

7. The method for producing an active material according to claim 1 , wherein the at least one alkali metal compound contained in the activation treatment agent contains the same alkali metal element as the alkali metal element contained in the active material.

8. 8. The method for producing an active material according to claim 1, wherein at least one of the alkali metal compounds contained in the activation treatment agent is an alkali metal compound that exhibits alkalinity when dissolved in water.

9. 9. The method for producing an active material according to claim 8, wherein the alkali metal compound that exhibits alkalinity when dissolved in water is at least one selected from the group consisting of hydroxides, carbonates, hydrogencarbonates, oxides, peroxides and superoxides of alkali metals.

10. The method for producing an active material according to any one of claims 1 to 9, wherein the activation treatment agent has a melting start temperature of 700°C or lower.

Citation Information

Patent Citations

  • Molten salt regeneration and repair method of lithium ion battery positive electrode material and obtained lithium ion battery positive electrode material

    CN110797602A

  • Method for recovering active material from discarded battery material

    JP2012186150A

  • Sodium ion secondary battery

    JP2016085890A

  • Composite cathode active material, method of preparing the same, and cathode and lithium battery including the composite cathode active material

    JP2019046795A

  • Positive electrode material for lithium secondary battery

    JP2019091655A